2017
DOI: 10.1249/mss.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Neural and Muscular Contributions to the Age-Related Reductions in Rapid Strength

Abstract: Age-related alterations in muscle quality (EI), architecture, and muscle activation may influence rapid torque production at late time intervals (≥100 ms) from contraction onset. These findings highlight specific neuromuscular factors that influence the age-related reductions in RTD, which has been shown to significantly influence function and performance in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 40 publications
6
86
4
Order By: Relevance
“…Additionally, the ability to recruit and activate motor units is also a known impairment in children and adolescents with spastic CP . Exploring if higher echo‐intensity values are related to reduced isometric force‐generation and rate of force‐generation, as seen in sarcopenia populations, would also provide another clinical meaning to higher echo‐intensity values in individuals with spastic CP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ability to recruit and activate motor units is also a known impairment in children and adolescents with spastic CP . Exploring if higher echo‐intensity values are related to reduced isometric force‐generation and rate of force‐generation, as seen in sarcopenia populations, would also provide another clinical meaning to higher echo‐intensity values in individuals with spastic CP.…”
Section: Discussionmentioning
confidence: 99%
“…ageing) (Gerstner et al . ) than maximal muscle force. Although previous studies have suggested that muscle activation is one of the key determinants of rapid force production, investigations into specific motor unit properties and their relationship to rapid strength are sparse.…”
mentioning
confidence: 90%
“…100–200 ms) (Gerstner et al . ). The later phase is thought to be more related to maximal strength, and thus muscle‐specific factors (i.e.…”
mentioning
confidence: 97%
“…Typically, rapid torque measures are examined at different time intervals of a muscle contraction such as the early (i.e., 0-50 ms) and late phase (i.e., 100-200 ms) [6,12]. Early rapid torque variables are associated with initial motor unit recruitment and firing rates [5,13], as well as intrinsic muscle properties (i.e., fiber type composition, calcium kinetics) [14,15], while maximal strength and muscle size become more influential for late rapid torque measures [14,16].…”
Section: Introductionmentioning
confidence: 99%